Discharge Availability Analysis of the Manikin Dam Using the F. J. Mock and NRECA Methods - A. H. Welkis, Wilberd; Krisnayanti, Denik Sri; Robson Klau, Ralno; Nait, Costandji; F. B. Welkis, Davianto; Doa Megonondo, Batara (Fakultas Teknik, Universitas Brawijaya, 2026)
East Nusa Tenggara is a semi-arid region with a relatively short rainy season and low annual rainfall of 1,250 mm/year. To address this condition, technical engineering measures are required, including the construction of water storage infrastructure, such as the Manikin Dam. Manikin Dam is located between Kuaklalo Village and Bokong Village, Taebenu District. This study aims to determine potential evapotranspiration using the Modified Penman Method and dependable discharge using two methods: the NRECA Method and the F.J. Mock Method. From these two methods, the one that best represents the characteristics of the Manikin watershed was selected. The results showed that the maximum half-monthly potential evapotranspiration in the Manikin watershed, calculated using the Modified Penman Method, is 97.7 mm, and the minimum is 44.2 mm. The average annual reliable discharge with the NRECA Method is 2.09 m3/s. The annual dependable discharge with the F. J. Mock Method is 1.35 m3/s. Of the two methods used, the NRECA Method is closest to the characteristics of the Manikin watershed, with an RMSE of 0.85. The filling time of Manikin Reservoir under normal water-years conditions is three months, from the first part (I) in December to the second part (II) in February. The time required to fill Manikin Reservoir for low-water-years conditions is three months, from the first part (I) of December to the first part (I) of March.